FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM SISTEM PENJUALAN SAYURAN - RATNA KOMALA DEWI; SUDIARTINI - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2001)
This research sought to identify (1) socio-economic factors influencing farmers’decision in selling fresh vegetables in Candikuning village, Tabanan regency, and (2)comparison between income of farmers utilizing Tebasan system and without Tebasansystem. Data was collected by using survey method. The 44 farmers with Tebasan systemand 20 farmers without Tebasan system have been chosen as a sample in this research. Timeperiod of the study was in planting season in June 1999 until September 1999. The data wasanalyzed by using Logit Function.The result of the study were (1) income’s farmers, need cash before harvesting timeand price risk influencing farmers’ decision in selling the fresh vegetables, and (2) there wasno income differences between both kinds of system.